FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DENGAN RISIKO BISNIS SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Andy Andy; Rossje V. Surya Putri (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
The objective of this research is to analyze: the influence of investment decision on .firm's value, the influence of financing decision on firm's value, the influence of dividend decision on firm 's value, the influence of firm's size on firm's value, the influence of business risk on firm's value, the role of business risk as intervening influence of investment decision on firm's value, the role of business risk as intervening influence of financing decision on firm's value, the role of business risk as intervening influence of dividend decision on firm's value, the role of business risk as intervening influence of firm's size on firm's value. The research was conducted in the companies listed in Indonesian Stock Exchange except for banks and other financial companies during 2011-2013 observation period. The total samples taken by using purposive sampling method were 110 companies out of 354 companies. Multiple regression and path analysis are used to analyze the hypothesis of this study. The result of this research using multiple regression finds that the investment decision, firm's size and business risk have influence toward firm's value. The financing decision and dividend decision do not have influence toward firm's value. The result of this research using path analysis finds that financing decision and firm's size have influence to firm's value with business risk as intervening variable. Investment decision and dividend decision do not have influence to.firm's value with business risk as intervening variable.